Role of supervisor in implementing a performance based culture in the organization and the experience of Banglalink GSM - Sakib, Md. Najmus (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.